2016
DOI: 10.1007/s00415-016-8339-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cerebral microbleeds on intracerebral hemorrhage and poor functional outcome of acute ischemic stroke patients treated with intravenous thrombolysis: a systematic review and meta-analysis

Abstract: It is still controversial whether pre-existing cerebral microbleeds (CMBs) increase the risks of intracranial hemorrhage (ICH) and poor functional outcome (PFO) in acute ischemic stroke (AIS) patients treated with intravenous thrombolysis (IVT). Therefore, we performed a systematic review and meta-analysis to determine the impact of CMBs on ICH and PFO of AIS patients with IVT. We searched PubMed, EMBASE and Web of Science from inception to August 3, 2016, with language restriction in English. We included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Having CMH causes 2.5 times more symptomatic intracerebral hemorrhage risk following IV tPA (43). However, this statistically significant risk increase was not shown in other studies (44).…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 62%
See 1 more Smart Citation
“…Having CMH causes 2.5 times more symptomatic intracerebral hemorrhage risk following IV tPA (43). However, this statistically significant risk increase was not shown in other studies (44).…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 62%
“…Although CMH causes a mild increase in bleeding rates, to make general and clear decisions, the efficacy of IV tPA in patients with CMH should be evaluated in randomized and controlled studies. There is an important point: the presence of CMH decreases the rate of good outcomes in patients both with and without bleeding following IV tPA (42,44,45). This could be related with small vessel dysfunction and insufficient control of risk factors.…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 99%
“…Although a recent meta-analysis concluded that cerebral microbleeds were not associated with symptomatic intracerebral hemorrhage (ICH) after intravenous thrombolysis, they were associated with poor functional outcome and various types of ICH. [ 3 ] Thus, patients with ICH without a prominent high density on NCCT, as in this case, should be treated with great care.…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting cerebral microbleeds have been considered a risk factor for BH after thrombolysis, and it was confirmed in three meta-analyses from pooled data of medical literature with 2702,[17] 1704,[18] and 2479[19] patients. According to three meta-analyses from 15/11/11 trials with a similar number of treated patients (6967/6912/7194), the presence of leukoaraiosis was associated with an increased risk of SICH and poor outcomes.…”
Section: Introductionmentioning
confidence: 86%